2011
DOI: 10.1002/cbic.201000672
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Safeguard against Mycotoxin Cyclopiazonic Acid Production in Aspergillus oryzae

Abstract: Aspergillus oryzae is a fungus widely used in traditional Japanese fermentation industries. Its inability to produce mycotoxins, due to mutation or transcriptional repression of the genes responsible for their biosynthesis, is consistent with the hypothesis that A. oryzae is a domesticated species derived from A. flavus, a wild species that is a well-known producer of aflatoxin. In contrast, the cyclopiazonic acid (CPA) biosynthetic gene (cpa) cluster in A. oryzae contains genes that have been lost in A. flavu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…1A). 1) We also found that cpaA is truncated by a telomere at the chromosomal end in CPA-nonproducing strain A. oryzae RIB 40 (Fig. 1A), 2) and that cpaH, which is deleted from the cpa cluster in A. flavus, is responsible for the synthesis of a new derivative of CPA, 2-oxoCPA, in CPA-producing strain A. oryzae NBRC 4177 (Fig.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…1A). 1) We also found that cpaA is truncated by a telomere at the chromosomal end in CPA-nonproducing strain A. oryzae RIB 40 (Fig. 1A), 2) and that cpaH, which is deleted from the cpa cluster in A. flavus, is responsible for the synthesis of a new derivative of CPA, 2-oxoCPA, in CPA-producing strain A. oryzae NBRC 4177 (Fig.…”
mentioning
confidence: 62%
“…The HPLC conditions were as in our previous study. 1) Chromatograms of the substrate solution fed to the fungal cultures showed a single peak of cAATrp at 19.9 min (data not shown). We confirmed that no Northern blot analysis of cpaA, cpaD, cpaO, and cpaH in the cpa cluster in A. oryzae RIB 40, NBRC 4177, and ÁcpaR, a gene disruption strain of cpaR in A. oryzae NBRC 4177.…”
mentioning
confidence: 96%
See 3 more Smart Citations